MENINGKATKAN PEMBERDAYAAN MASYARAKAT TERHADAP UMKM MELALUI E - DIGITAL DI KELURAHAN GAJAHMUNGKUR - Kurniawati, Endang; Zulfa, Intan Amalina; Andani, Berliana Indah; Salsabil, Ahmad Rivaldi; Saudah, Nurus; Iqbal, Fariez (STIE Pelita Nusantara, 2025)
AbstractIn the growing E- digital era, the use of information and communication technologies has been a key factor in the survival and growth of micro, small, and medium enterprises (MSMEs). SMEs constitute the backbone of Indonesia’s reeconomy, contributing significantly to gross domestic product (GDP) and labor absorption. However, many SMEs still face challenges in accessing wider markets, promoting products, and increasing competitiveness. SMEs in Indonesia play a very vital role in the reeconomy, contributing almost 60% to GDP and absorbing a lot of labour. However, many SMEs are still lagging behind in terms of marketing, especially in utilizing E- digital technologies as per the current conditions. Many SME actors are yet to realize the importance of E- digital marketing to enhance their competitiveness and reach a wider market. the empowerment of SMEs through E - DIGITAL MARKETING, along with the rapid development of information technologies that are changing the way businesses operate.Keywords: the use of information and communication technologies, promoting products, and increasing competitiveness. E - DIGITAL MARKETING